Moral Message in The Fabel “Ant Struggle” by Aleanzah as A Cultivation Of Peace-Loving Character Education in Junior High School Children - Adinda Erdiana; Nazla Maharani Umaya (Universitas PGRI Semarang, 2019)
The purpose of this paper is to describe the moral message contained in the label